The Influence of Personality, Motivation, Brand Image, and Environment on Students’ Intention in Choosing Bogor Agricultural University (IPB) - Solikhah, Aris; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
The research aimed to identify the level of intention and analyze the influence of personality, motivation, brand image, and environment on intention of the top 15 grade of 11 Science students from 14 high schools in Jakarta, Bogor, Depok, Tangerang, and Bekasi to choose IPB and its managerial implications. Questionnaire with Likert scale was used as a method in collecting data. Descriptive and Structural Equation Modeling (SEM) was used in analyzing data. The results showed that one of three students intended to apply to IPB as a sequence of first choice and second choice. Brand image and motivation significantly influenced the students’ intention in choosing IPB. Environment and personality did not influence the intention. Environment significantly influenced brand image and students’ motivation. Personality did not influence the motivation, brand image, and intention. Making marketing strategies related to students’ intention, IPB should consider motivational factors; e.g., students’ preference in science and agricultural technology, brand image (good reputation), and environment (counseling teachers’ advice and access to the internet/website) in choosing a college as a main factor. Keywords: brand image, environment, intention to choose IPB, motivation, personality Penelitian bertujuan mengidentifikasi tingkat niat dan menganalisis pengaruh kepribadian, motivasi, brand image, dan lingkungan terhadap niat 15 siswa terbaik IPA kelas XI tahun ajaran 2014/2015 di 14 SMA JABODETABEK dalam memilih IPB serta implikasi manajerialnya. Metode pengambilan data menggunakan kuesioner dengan skala likert. Analisis data yang digunakan deskriptif dan Structural Equation Model (SEM). Hasil penelitian ini menunjukkan satu dari tiga siswa berniat mendaftar ke IPB sebagai urutan pilihan pertama dan pilihan kedua. Brand image dan motivasi berpengaruh signifikan terhadap niat siswa memilih IPB. Lingkungan dan kepribadian tidak berpengaruh terhadap niat. Lingkungan berpengaruh signifikan terhadap brand image dan motivasi siswa. Kepribadian tidak berpengaruh terhadap motivasi, brand image, dan niat. IPB dalam membuat strategi pemasaran yang berhubungan minat siswa hendaknya mempertimbangkan faktor motivasi (menyukai bidang sains dan tekologi bidang pertanian), brand image (reputasi baik) dan lingkungan (pertimbangan guru Bimbingan Konseling dan akses internet/website) dalam memilih perguruan tinggi sebagai faktor utama.Kata kunci: brand image, kepribadian, lingkungan, motivasi, niat memilih IPB